Comparison of different types of phacoemulsification tips. III. Morphological changes induced after multiple uses in an ex vivo model. Issue 1 (January 2018) - Tsaousis, Konstantinos T.; Chang, David F.; Werner, Liliana; Perez, Jesus Paulo; Guan, Jia J.; Reiter, Nicholas; Li, He J.; Mamalis, Nick
Abstract : Purpose : To assess the ultrastructural morphologic changes in the surface's micro‐roughness for single‐use and multiple‐use phaco tips after multiple phacoemulsification cycles in an ex vivo animal model. Setting : John A. Moran Eye Center and Utah Nanofab, College of Engineering, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Eight types of phaco tips were studied using an identical experimental protocol. Two tips of each type were used to emulsify porcine cataractous lenses of moderate hardness for 2 minutes. This cycle was then repeated 5 consecutive times for each phaco tip. Scanning electron microscopy and white‐light interferometry were used to analyze each tip for potential ultrastructural damage. Results : No significant structural damage was noted on either single‐ or multiple‐use tips after 5 cycles of experimental use. There was a trend toward increased surface micro‐roughness at the tip opening after multiple procedures. Most tips had salt crystals on their surface and deposits of organic material composed of carbon and oxygen, which were consistent with porcine tissue that had not been cleaned from the tip surface. Conclusions : No significant ultrastructural damage was detected after repeated experimental use of phaco tips in a porcine cataract model. There was no significant difference when phaco tips labeled for single use or multiple uses were compared.